The Cultural and Religious Dimension of Russia and the Orthodox World in the 17th Century in the Interpretation of Slavophiles - A. V. Skizhenok (Vestnik MGIMO-Universiteta)
This article is a review of the recently published Russian translation of Andrzej Valitsky’s monograph “In the circle of conservative utopia. The structure and metamorphoses of Russian Slavophilism”. The publication of the monograph of the Polish historian and philosopher in Russian last year was accompanied by considerable interest both in the conclusions of the author himself and in the topic that he touched on in the book. The purpose of this review is not so much to convey the contents of Andrzej Valitsky’s book, but to analyze the validity of his individual conclusions and the degree of objectivity of the proposed view on the history of Slavophilism and the degree to which it is conditioned by the events of Russian history.